The Song Cycle of the Epic Dzhangar by Eelyan Ovla: Experience in Quantitative Analysis - N. Ochirova; S. Bachaeva; N. Mulaeva (Oriental Studies, 2018)
The research provides a detailed and thorough statistical analysis of the Dzhangar text, the cycle of songs by Eelyan Ovla. As a result of statistical processing, the frequency of use of lexical units was presented in the table, which consists of 4 columns: I - rank, II - word, III - absolute frequency, IV - relative frequency. There are frequent lexems of the biggest Ch.1 - “Khongrin ger avlghna byelg” in the table 1. It contains 96 lexems, among which the lexeme gikh is the most frequent (170 lexems), and the least frequent is the numeral zurgan (11 lexems). The table 2 presents the most frequent lexemes from all the Chapters. Since the Ch.10 is not so big, it presents only 4 lexemes. The most common among frequent lexemes of the first rank is the verb gikh, which is peculiar to all Mongolian languages and is usually found in the texts with participle and gerund forms such as: gisn, gidg, gizh’, gikhlya and are predominant in five Chapters, though it takes the second or the third place in the other Chapters. The bar charts clearly demonstrate the occurrence and distribution of color and number symbolism in all Chapters of the epic as well as the total number of more common word forms. According to the second bar chart, the most commonly used numeral is khoir - “two” - 228 (word usage), as it is used in the text not only as numeral but as a conjunction “and”; then follows minghn “thousand” - 166 (words usage). According to statistical data of the given cycle, the most common lexemes, denoting color are khar “black”, tsagan “white”, shar “yellow”, ulan “red”, kyek “blue”. Apart from the five main colors one can find bor (2) i.e., “grey”, e.g.: “Bor uul, Borzatyn bor tolgha.” Having analyzed all the obtained statistical data, the researchers conclude that the most common lexemes are: among verbs - gikh, byayakh, gikh; among numerals - khoir, minghn; among colors - khar, tsagan; and most common negative particle is uga. Quantitaive data, based on the epic cycle of songs by Eelyan Ovla, help to clarify the principles of the incorporation of the units into the dictionary. Due to the illustration of the quantitaive characteristics of a word in the defining dictionary one can see the frequency of a particular element in the text of the epic Dzhangar.